(untitled) (Docentes 2.0 Journal, 2025)
Over the past few decades, school coexistence has become increasingly important, particularly in light of the challenges facing new generations regarding diversity, inclusion, and conflict prevention. The objective of this research was to determine the relationship between social exclusion and school coexistence. The study employed a deductive method with a quantitative approach, utilizing a non-experimental, correlational, and cross-sectional design. The sample consisted of 210 students, with two Likert-type scales applied for quantitative analysis. The results yielded a significant level of p < 0.000 and a Rho value of -0.757, demonstrating that social exclusion and poor social coexistence can lead to social isolation of students due to a lack of integration into the group, which can generate disruptive behaviors. In conclusion, it was argued that a relationship exists between social exclusion and school coexistence, but the disconnection between these two factors minimizes this relationship. When students were marginalized in the school environment due to social, cultural, and economic differences, tensions and conflicts arose in the interactions inherent to student life.